Pengaruh Kompetensi Aparatur Desa dan Sistem Pengendalian Intern Terhadap Kualitas Pelaporan Keuangan Desa Serta Dampaknya pada Pengelolaan Dana Desa Sebagai Variabel Intervening: Studi Empiris Kecamatan Kabila Bone Kabupaten Bone Bolango Provinsi Goronta - Fristi Nanda Wilanda; Usman; Victorson Taruh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of village apparatus competency and internal control systems on the quality of village financial reporting and its impact on village fund management in Kabila Bone District, Bone Bolango Regency, Gorontalo Province. This research uses quantitative research methods. The data collection technique used in this research is primary data obtained from questionnaires distributed to the village head, Secretary, Head of Finance, Head of Planning, Village Consultative Body (BPD) and all Hamlet Heads in each village in Kabila Bone District, Bone Bolango Regency. The data analysis technique in this research is descriptive statistics with inner model and outer model tests using Partial Least Squares - Structural Equation Model (PLS-SEM). Based on the results of this research, it shows that the competence of village officials has a positive and significant effect on the quality of village financial reporting with a significance level of 0.0038<0.05, so hypothesis I is accepted. The competency of village officials has a positive and significant effect on village fund management with a significance level of 0.0008<0.05, so hypothesis II is accepted. Village fund management has a positive and significant effect on the quality of village financial reporting with a significance level of 0.0064<0.05, so hypothesis III is accepted. The internal control system has a negative and insignificant effect on the quality of village financial reporting with a significance level of 0.9468>0.05, so hypothesis IV is rejected. The internal control system has a positive and significant effect on village fund management with a significance level of 0.0077<0.05, so hypothesis V is accepted. The competency of village officials has a positive and significant effect on the quality of village financial reporting through village fund management with a significance of 0.0289<0.05, so hypothesis VI is accepted. The internal control system has a negative and insignificant effect on the quality of village financial reporting through village fund management with a significance of 0.0831>0.05, so hypothesis VII is rejected.